Chrysolampine Wasps (Chalcidoidea: Perilampidae sensu lato) From Baltic Amber. Issue 6 (13th December 2019) - Burks, Roger A; Krogmann, Lars; Heraty, John M
Abstract: Chrysolampine wasps belong to a unique lineage of Chalcidoidea characterized by mobile first instar larvae and known as the planidial clade. The fossil history of this biologically highly derived group of parasitoids is still little known due to the scarcity of preserved fossils. Here, we report the discovery of four specimens of Chrysolampinae from Eocene Baltic amber, representing the first fossil record for the subfamily. All specimens can be assigned to the extant genus Brachyelatus Hoffer & Novicky and are described as Brachyelatus marthae sp. nov. Brachyelatus is characterized by a number of putative plesiomorphies, such as a short petiole and a smoothly sloping pronotum. Synapomorphies with other Chrysolampinae include pores in sloping depressions on the male scape, shape of the clypeus, and features of the fore wing venation. The fossils differ from all examined extant members of Chrysolampinae by the arrangement of the uncal sensilla on the fore wing stigma in a straight line.